A Novel Approach in Raman Temperature Sensing in Optical Fiber based on Broadband Incident Light - Renner, Esther; Härteis, Lisa-Sophie; Weiss, Nico; Schmauß, Bernhard (OSA Technical Digest, 2021)
We describe a new approach in Raman temperature sensing based on broadband incident light. The reported results show the proof of concept and thus form an important basis for future distributed temperature sensing systems.